Dahuang—Taoren, a botanical drug combination, ameliorates adenomyosis via inhibiting Rho GTPases - Lei, Ya; Fu, Xianyun; Chen, Minmin; Yi, Yongli; Mao, Ping; Peng, Li; Qu, Zhao (Frontiers in Pharmacology, 2023)
Dahuang - Taoren (DT) is a classic combination of botanical drugs applied to treat pain-related diseases in ancient China. Today, DT is frequently applied for dysmenorrhea of adenomyosis (AM) in the clinic. Growing evidence indicates Rho GTPases may play an essential role in AM progression. However, the potential mechanism of DT on Rho GTPases in AM remains unclear. To this end, the expressions of Rho GTPases in the patients with AM were evaluated. Further, pituitary transplantation-induced AM mice and the primary AM endometrial stromal cells (AMESCs) were subjected to DT intervention. The results revealed that the expressions of Rho GTPases were significantly up-regulated in both AM patients and AM mice. The DT could reduce pathological infiltration, relieve hyperalgesia, and alleviate cytoskeleton remodeling in AM mice. Besides, the migration and invasion of AMESCs were markedly inhibited after exposure to DT. These effects may be linked to the decreased Rho GTPases expression. The results may offer a novel explanation of DT against AM.